Identification of Amino Acids Present in The Leaves and Stem of Ipomoea carnea - KHATIWORA, E.; ADSUL, V.B.; DESHPANDE, N.R. (Asian Journal of Chemistry, 2010)
Air shade dried powdered material of stem and leaves were used for detection of amino acids from Ipomoea carnea. Paper chromatographic technique was used with different mobile phases. Specific amino acids were detected in specific mobile phases. The obtained amino acids were identified by comparing with standards. Total 18 amino acids in the leaves and 7 amino acids in the stem were detected. Two mobile phases were found suitable for the amino acids present in the leaves and only one for those present in the stem.